Appropriate Percutaneous Coronary Intervention - Haq, M Maksumul; Ahsan, Chowdhury H (Ibrahim Cardiac Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/icmj.v2i1.17380 Ibrahim Cardiac Med J 2012; 2(1): 5-7